A Dynamic Process Model for Finding Informants and Gaining Access in Qualitative Research. (July 2016) - Peticca-Harris, Amanda; deGama, Nadia; Elias, Sara R. S. T. A.
This article surfaces some of the emotional encounters that may be experienced while trying to gain access and secure informants in qualitative research. Using the children's game of hopscotch as a metaphor, we develop a dynamic, nonlinear process model of gaining access yielding four elements: study formulation with plans to move forward, identifying potential informants, contacting informants, and interacting with informants during data collection . Underlying each element of the process is the potential for researchers to re-strategize their approach or exit the study. Autobiographical stories about gaining access for our PhD dissertation research are used to flesh out each element of the process, including the challenges we experienced with each element and how we addressed them. We conclude by acknowledging limitations to our study and suggest future and continued areas of research.